Undergraduates’ Preferences and Information Use Behaviour - Chohda, Nirupma; Kumar, Shiv (Journal of Information and Knowledge, 2019)
The current study is a descriptive survey of undergraduate students of the National Institute of Technology, (NIT), Srinagar. The lacunae observed may lead to a better understanding of the information needs of present day college students and how they are satisfying these information needs. A survey was conducted from April to June 2017. A questionnaire was distributed to 130 undergraduate students of NIT, Srinagar. Out of which 107 filled-in questionnaires were returned. The disproportionate random sampling method was adopted. The study revealed that library is regularly used and there is a notable change in using the library resources by the undergraduates. The web resources are used scarcely. It is envisaged that the study will benefit the NIT library to improve their resources as per the need and demands of the users.